POLA PEMBIASAAN ORANG TUA MENDIDIK ANAK MEMBACA AL-QUR’AN DALAM RUMAH TANGGA DI PERUMAHAN BUKIT DEWA RESIDEN RT 03 RW 01 KELURAHAN SUMUR DEWA KECAMATAN SELEAR KOTA BENGKULU - Fajar Kurniawan (UIN Fatmawati Sukarno Bengkulu, 2019)
This study aims to To reveal the parenting pattern of parents in educating their children in reading the Qur’an in their family. This research is a field research (field research), with descriptive qualitative method. Data collection was conducted using unstructured interviews, selected observation and documentation. Data processing with editing, classification, data analysis and conclusion. The results showed that: 1) The pattern of parents’ habituation to educate children in reading the Qur’an in Resi- dential Bukit Dewa Resident RT 03 RW 01 Village Sumur Dewa District Selebar Kota Bengkulu runs quite well, educate children read the Qur’an by sending children to study in the mosque and bring teachers to study home. The patterns used are through direct approach, exemplary patterns, patterns of habituation, patterns of advice, patterns of punishment and giving rewards. 2) Example of parent to educate their children in reading the Al-Qur’an has not been realized properly. Among the lesser causes are: first the laziness of the parents themselves, second because of busy in the work of parents. 3) Form of evaluation provided by parents in habituation to educate children reading the Al-Qur’an has been going pretty well. First of all with praise and flat- tery, second by giving gifts, third by giving punishment. 4) Parental obstacles in educating children reading the Qur’an include: first factor self, second the number of tasks from school, third factor of parents, fourth environmental factor of society